The Actin Regulator Coronin-1A Modulates Platelet Shape Change and Consolidates Arterial Thrombosis - Stocker, Thomas J.; Pircher, Joachim; Skenderi, Artid; Ehrlich, Andreas; Eberle, Clemens; Megens, Remco T. A.; Petzold, Tobias; Zhang, Zhe; Walzog, Barbara; Müller-Taubenberger, Annette; Weber, Christian; Massberg, Steffen; Ishikawa-Ankerhold, Hellen; Schulz, Christian (Thrombosis and Haemostasis, 2018)
Coronin-1A (Coro1A) belongs to a family of highly conserved actin-binding proteins that regulate cytoskeletal re-arrangement. In mammalians, Coro1A expression is most abundant in the haematopoietic lineage, where it regulates various cellular processes. The role of Coro1A in platelets has been previously unknown. Here, we identified Coro1A in human and mouse platelets. Genetic absence of Coro1A in mouse platelets inhibited agonist-induced actin polymerization and altered cofilin phosphoregulation, leading to a reduction in spreading and low-dose collagen induced aggregation. Furthermore, Coro1A-deficient mice displayed a defect in ferric chloride-induced arterial thrombosis with prolonged thrombus formation and reduced thrombus size. Immunofluorescence analysis revealed a less compact thrombus structure with reduced density of platelets and fibrinogen. In summary, Coro1A has a role in platelet biology with impact on spreading, aggregation and thrombosis.
Keywords: coronin-1A; coro1A; platelets; thrombosis; actin